Mapping and Correlation Analysis of Efficiency and Profitability: The Case of Islamic Rural Bank in Indonesia - Titi Dewi Warninda; M. Nadratuzzaman Hosen (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
This research aims to analyze efficiency and profitability of Islamic Rural Banks in Indonesia using Variable Returns to Scale model of Data Envelopment Analysis and efficiency-profitability matrix. The results of this research show that most of Islamic Rural Banks are included in the Dog quadrant (high efficiency but low profitability) and Sleeper quadrant (low efficiency but high profitability). Meanwhile, the result of correlation analysis between efficiency and profitability indicates that efficiency has a negative correlation with profitability. Negative correlation of efficiency and profitability is in accordance with the result of efficiency-profitability matrix. The results of this research show that not all of Islamic Rural Bank which have high efficiency are also having high profitability.DOI:10.15408/aiq.v7i1.1354